Metabolic Syndrome and Its Components: Secondary analysis of the World Health Survey, Oman - Mahmoud Abd El-Aty (Sultan Qaboos University Medical Journal, 2014)
Objectives: The study aimed to describe the prevalence of metabolic syndrome (MS) and its components among Omani adults. Methods: The 2008 Oman World Health Survey dataset was used to determine the national prevalence of MS. Logistic regression using all key sociodemographic, clinical and behavioural variables was used to identify the associations of independent variables with MS. Results: The age-adjusted prevalence of MS was 23.6%. MS was significantly associated with age, marital and work status and wealth level. MS was more common for people aged 50 years and older compared to the youngest cohort (OR 3.6, CI: 2.4–5.3; P <0.001) and in people who were married or employed (OR 1.6, CI: 1.3–2.1; P <0.001 and OR 1.3, CI: 1.1–1.8; P = 0.043, respectively) compared to their unmarried and unemployed counterparts. MS was also more common in people in the second lowest wealth quintile (OR 1.6, CI: 1.2–2.2; P = 0.05) compared to the lowest quintile and in those who sat for more than six hours per day (OR 1.3, CI: 1.1-1.7; P = 0.035). Conclusion: One in four adults had MS in Oman. This may fuel the epidemic of non-communicable diseases (NCDs) in Oman, particularly given the increasingly elderly population. Urgent action is required to ensure quality patient care at all levels of the healthcare system. Further research on behavioural risk factors is needed. Developing and implementing a multisectoral strategy to prevent NCDs should be at the top of the current health agenda for Oman.